The Effect of a Class Visit Supervision Workshop on the Pedagogic Abilities of Basic School Teachers Assessed from Early Pedagogic Ability in Rantau Selatan District, Labuhanbatu District - Menneria Pane; Ajat Sudrajat; Titi Chandrawati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This type of research used in this research is experimental quantitative research. To find out the effect of the classroom visit supervision workshop and teacher certification on the pedagogical ability of elementary school teachers in terms of the initial pedagogical ability in Rantau Selatan District. The population in this study was elementary school teachers in Rantau Selatan District, Labuhanbatu Regency, totalling 377 teachers spread over 23 locations. The sample in this study was 60 teachers. From the research results, it can be concluded that the magnitude of the simultaneous influence of the implementation of the supervisory workshop and the initial ability to the pedagogical ability of teachers is 66.4% while the remaining 33.6% is influenced by other factors outside of the two variables observed in this study.